Cost-Effectiveness of UGT1A1*28 Genotyping in Preventing Severe Neutropenia Following FOLFIRI Therapy in Colorectal Cancer. - Solen Pichereau; Anne Le Louarn; Thierry Lecomte; Hélène Blasco; Chantal Le Guellec; Hélène Bourgoin (Journal of Pharmacy & Pharmaceutical Sciences, 2011)
PURPOSE: Functional polymorphisms of the UGT1A1 gene, particularly the UGT1A1*28 variant, are associated with the severity of the bone marrow suppression in patients with metastatic colorectal cancer receiving irinotecan. This study assesses the cost-effectiveness of screening for UGT1A1*28 polymorphism associated with primary prophylactic Granulocytes Colony Stimulating Factor in patients homozygous for the *28 allele. The effectiveness was estimated based on the number of neutropenia avoided. METHODS: We modelled a theoretical population treated with combined 5-fluorouracil, leucovorin and irinotecan (FOLFIRI) for metastatic colorectal cancer. A decision tree simulated the health outcomes, measured by the prevalence of neutropenic events for two strategies, with or without UGT1A1 genotype screening. The model incorporated direct hospital costs and was validated with a sensitivity analysis. We calculated the cost-effectiveness ratio: CE=∆C / ∆E = "genotyping" cost – "no genotyping" cost / number of febrile neutropenia avoided. RESULTS: In the "genotyping strategy", the cost to avoid one febrile neutropenia event per 1000 patients treated was € 942.8 to € 1090.1. The sensitivity analysis showed a better CE ratio of € 733.4 to € 726.6 per febrile neutropenic event avoided.CONCLUSIONS: UGT1A1 genotype screening before irinotecan treatment is a cost-efficient strategy for the hospital. Systematic genotyping prior to chemotherapy, and administration of CSF in patients homozygotes for the *28 allele allow to avoid 91 febrile neutropenias at an acceptable cost.